The development of an intrinsic programmed instruction text for use in systems performance and maintenance evaluation training - Martin, David (Quezon City [s.n.], 1972)
The problem of this study is to develop and test an intrinsic programmed text for use in SPAME training. The text is constructed so as to satisfy the requirements of a prescribed set of behavioral objectives.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Programmed instruction; Systems Performance and Maintenance Evaluation